The effect of teachers' perceptions of the TAM learning model seen on the student’s learning outcomes in high school - Ugi Nugraha; Ekawarna Ekawarna; Muhammad Ali; Try Arianto Adhanegara (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
Technology is an important aspect in improving the process of student development This study attempts to examine how are the descriptive results of teacher perceptions and student learning outcomes and how are the perceptions of the application of the tam model applied to student learning outcomes. The sample of this research is as many as fifty teachers who teach subjects physical education with a working period of 1-8 years and 9-16 years. The method used in this research is a mixed method with quantitative data as primary data and qualitative data as reinforcing data. In the results obtained, it can be seen that there is an influence between teacher perceptions of the Technology Acceptance Model (TAM) learning model which measures the level of understanding of students in interactive multimedia learning media on student learning outcomes, and the results of teacher interviews that today's technology needs are very important to improve learning. Therefore, this test is very important because there are no researchers who have tested these variables and there is an influence from the variables being tested. Therefore, this study aims to examine the results of descriptive statistics on teacher perceptions seen from student learning outcomes, and measure the effectiveness of the perception of the application of the Tam model on student learning outcomes.